Timeline editing of objects in video - Lu, Shao-Ping (IEEE transactions on visualization and computer graphics, 2013)
We present a video editing technique based on changing the timelines of individual objects in video, which leaves them in their original places but puts them at different times. This allows the production of object-level slow motion effects, fast motion effects, or even time reversal. This is more flexible than simply applying such effects to whole frames, as new relationships between objects can be created. As we restrict object interactions to the same spatial locations as in the original video, our approach can produce highquality results using only coarse matting of video objects. Coarse matting can be done efficiently using automatic video object segmentation, avoiding tedious manual matting. To design the output, the user interactively indicates the desired new life spans of objects, and may also change the overall running time of the video. Our method rearranges the timelines of objects in the video whilst applying appropriate object interaction constraints. We demonstrate that, while this editing technique is somewhat restrictive, it still allows many interesting results